2000
DOI: 10.1016/s0893-133x(99)00110-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Rearing Environment on the Development of GABAA and Central Benzodiazepine Receptor Levels and Novelty-Induced Fearfulness in the Rat

Abstract: We compared the effects of handling or maternal separation from the day following birth until postnatal day 14 on behavioral responses to novelty and on GABA A and central benzodiazepine (CBZ) receptor levels in the rat. As adults, handled animals showed reduced startle responsivity, increased exploration in a novel open field, and decreased novelty-induced suppression of feeding relative to the handled (H) and/or maternal separation (MS) groups. As compared with handled animals, both nonhandled (NH) and MS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
337
4
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(372 citation statements)
references
References 57 publications
20
337
4
11
Order By: Relevance
“…3C shows the lack of a negative trend). Power tests showed that our study would have been able to detect an effect size comparable to that reported by Caldji et al (2000). Including marked and unmarked rats (because marking had no significant effect on this test), we would have had a power of .99 to detect the magnitude of difference they report in latency to feed between EH and NH rats (minimum n ¼ 19 per cleaning treatment group; hypothesized effect size (arcsine transformed) ¼ .73; standard deviation ¼ .49; a ¼ .05).…”
Section: Figuresupporting
confidence: 74%
“…3C shows the lack of a negative trend). Power tests showed that our study would have been able to detect an effect size comparable to that reported by Caldji et al (2000). Including marked and unmarked rats (because marking had no significant effect on this test), we would have had a power of .99 to detect the magnitude of difference they report in latency to feed between EH and NH rats (minimum n ¼ 19 per cleaning treatment group; hypothesized effect size (arcsine transformed) ¼ .73; standard deviation ¼ .49; a ¼ .05).…”
Section: Figuresupporting
confidence: 74%
“…Animal models support the notion that stress and trauma can alter GABA A -benzodiazepine binding density. 2,6,[36][37][38] In general, these animal models have shown decreased GABA A function and binding in the cerebral cortex and hippocampus. [3][4][5] This is the first benzodiazepine-GABA A receptor binding study in patients with PTSD that supports these preclinical data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these HPA effects, offspring of low LG dams have a decreased density of benzodiazepine receptors in the amygdala compared to the offspring of High LG dams [36;38;39;40] and GABA subunit expression is altered by maternal LG with implications for …”
Section: Influence Of Maternal Care On Offspring Neurobiology and Behmentioning
confidence: 99%
“…Interestingly, in these initial studies, a negative linear correlation was demonstrated between the levels of maternal LG received and adult plasma levels of corticosterone following restraint stress [36]. Behaviorally, these neuroendocrine changes result in decreased exploratory behavior and increased inhibition on tests such as the open-field and elevated plus maze [35].In addition to these HPA effects, offspring of low LG dams have a decreased density of benzodiazepine receptors in the amygdala compared to the offspring of High LG dams [36;38;39;40] and GABA subunit expression is altered by maternal LG with implications for …”
mentioning
confidence: 99%